Studying Some Factors That Increase the Risk of Thalassemia in The City of Baquba - Sara Fawzi Sahm (Journal of Techniques)
In the current study, 200 cases with thalassemia (111 males and 89 females) were used. Case samples were obtained from persons listed for Baquba Teaching Hospital / Hematology Center from November 1st, 2019 to January 31, 2020. Data were taken from patients' get-in hospital clinical reports through a form prepared for collecting data. The study aims to measure the impact of some factors on Thalassemia. The results showed that there is an effect of the relationship between chronological age and getting the disease, as it was found that the highest percentage was within the age group (1-10) years. It was also found that the number of males carry the disorder is higher than the number of infected females. Also, the effect of the type of Thalassemia factor on the infection of the disease shows that those who carry thalassemia major are more affected than those who carry thalassemia intermedia. The effect of the blood type factor on the infection rate shows that the highest number of infected people was those with blood type O. The effect of the disease history factor on the infection of the disease shows that the category (less than one year old) is more likely to get the disease. The effect of the factor of the number of infections in the family shows that the category (there are no previous infections in the family) are more numerous.